PERSIAN PHILOSOPHY IN THE ARCHIPELAGO: The Transmission of Persian Islamic Intellectual Tradition to Indonesia in the Contemporary Era - Ja'far, Ja'far; Lubis, Dahlia; Iqbal, Muhammad (Journal of Contemporary Islam and Muslim Societies, 2023)
Abstract: The majority of Muslims in Indonesia adhere to the Sunni school, but a small number of Muslims in this country adhere to the Shia Imamiyah school, which has been actively involved in developing the Islamic intellectual tradition of Persia (Iran), currently the center of intellectual and spiritual Shiism in the world. This study examines the transmission of the Persian Islamic intellectual tradition to the archipelago in the contemporary era. The study is a literature review, employing the social history approach. It argues that translation activities carried out by individuals or groups of Shia Muslims in Indonesia, as well as scientific research conducted by some students and lecturers at Islamic universities in Indonesia, has become the most important factors in the process of transmitting philosophy from Persia to Indonesia. This study enriches the understanding of the history of Islamic philosophy in Indonesia. This study argues that Persian philosophy has influenced the development of Islamic philosophy in Indonesia. Keywords: Islamic philosophy, Persian, Archipelago, Islamic intellectual tradition